Vitamin D Levels in Adults with Crohn's Disease Are Responsive to Disease Activity and Treatment. Issue 5 (27th March 2014) - Ham, Maggie; Longhi, Maria S.; Lahiff, Conor; Cheifetz, Adam; Robson, Simon; Moss, Alan C.
Abstract : Background: Vitamin D deficiency is common in patients with Crohn's disease (CD), although whether this impairs immune responsiveness, and is related to disease activity per se, remains unclear. We sought to investigate vitamin D pathways in patients with CD according to measures of inflammation and immune response. Methods: Prospectively collected samples of a well-characterized cohort of patients with CD were used to measure serum 25(OH)-vitamin D levels by enzyme-linked immunoassay. Related gene expression was determined by polymerase chain reaction in T cells. The effect of vitamin D on the proliferation of isolated CD4 + cells was determined. Results: Patients with active CD had lower serum vitamin D levels than those in clinical remission; this measurement was independent of season or reported use of vitamin D supplements. Harvey–Bradshaw Index scores, but not C-reactive protein, correlated with serum vitamin D levels. Gene expression of the vitamin D receptor was higher in peripheral blood T cells from patients with active disease than in those in remission. The proportion of CD25hi CD4 + cells from patients with CD increased in the presence of vitamin D. After treatment with infliximab, significant increases in serum vitamin D levels were noted in patients. Conclusions: Low vitamin D levels are associated with disease activity in CD and increase after infliximab treatment.